A proposal on a new curriculum for the smart eco-efficient built environment - Pacheco-Torgal, F. (2016)
Several authors reported a severe reduction in undergraduate applications to civil engineering in different countries. This fact will lead to a severe shortage of civil engineers in the coming years. These professionals will be especially needed to tackle infrastructure construction and rehabilitation on a context of climate change and increased world population. Part of the explanation for the low attraction capability of civil engineering relates to the fact that this course is viewed as low tech. A scientific and technical upgrade of the civil engineering curriculum is, therefore, needed. Nano and biotech based materials and technologies for the built environment could refresh the attraction of this area. The environmental challenges faced by a Planet that has about 220,000 new inhabitants each day and that will have more than 9,7 billion people by 2050 and 11,2 billion by 2100 means that a strong eco-efficiency focus of the new curriculum is also needed. On this context a proposal on a new curriculum on Smart Eco-Efficient Built Environment is suggested that could provide the construction market with professionals with a set of new and enhanced holistic high tech skills.